2011
DOI: 10.1209/0295-5075/96/27013
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of lithium-doped graphane for hydrogen storage

Abstract: Based on the first-principle density functional calculations we predict that Li-doped graphane (prehydrogenated graphene) can be a potential candidate for hydrogen storage. The calculated Li-binding energy on graphane is significantly higher than the Li bulk's cohesive energy ruling out any possibility of cluster formations in the Li-doped graphane. Our study shows that even with very low concentration (5.56%) of Li doping, the Li-graphane sheet can achieve a reasonable hydrogen storage capacity of 3.23 wt.%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…The binding energy is estimated to be -2.3 eV per Li atom. A significant decreasing trend in the binding energies of the Li doped graphane sheet while increasing the Li doping concentration from 50% to 3.12% has already been reported in previous studies 36,37 . At higher doping concentration, the possibility of clustering between the Li adatoms ultimately lowers the binding energies of the Li doped graphane sheet; thus a 3.12 % of Li doping concentration is carefully maintained for this current study.…”
Section: Structural Properties Of Li-doped Graphanesupporting
confidence: 74%
“…The binding energy is estimated to be -2.3 eV per Li atom. A significant decreasing trend in the binding energies of the Li doped graphane sheet while increasing the Li doping concentration from 50% to 3.12% has already been reported in previous studies 36,37 . At higher doping concentration, the possibility of clustering between the Li adatoms ultimately lowers the binding energies of the Li doped graphane sheet; thus a 3.12 % of Li doping concentration is carefully maintained for this current study.…”
Section: Structural Properties Of Li-doped Graphanesupporting
confidence: 74%
“…9,11 For an efficient and reversible hydrogen storage medium, it is advisable to have hydrogen adsorbed in molecular form with adsorption energy in the range of 0.1 to 0.4 eV/H 2 . [9][10][11]13 A potential storage material of H 2 would have large surface area and low molecular weight. The US Department of Energy (DOE) has set an ultimate goal that the gravimetric density of H 2 should exceed 7.5 wt %.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no literature on the Li adatom above the V CH vacancy, a few studies of Li on pristine graphane are available. [33][34][35][36][37] It has been reported that the single Li adatom prefers to bind with the substrate as opposed to the Li clusters, at zero kelvin. [33][34][35][36] The Li adatom introduces mid-gap states within the graphane band gap.…”
Section: Introductionmentioning
confidence: 99%